Estratégia de desenvolvimento sustentável na produção florestal em pequenas propriedades tabacaleiras - Teixeira, Debora da Silva (2021)
As an economic activity, forests were and remain strategic for the development of Brazil. The growing search for alternatives to replace fossil fuels highlights the forest production importance. Among the various sectors that use wood for energy, tobacco production stands out; an activity developed mainly in small farms which demands large quantities of firewood annually to cure tobacco leaves. In this context, the work presented here intends to analyze forest production and the consumption of firewood in tobacco farms in southern Brazil and identify its potential for promoting sustainable development in small rural properties. To fulfill this objective, the importance of firewood as input for tobacco production and the sustainability of supply was investigated; bottlenecks and opportunities for the economic development of small tobacco farms through forest products have been identified, and a management tool has been developed through the creation of a sustainability index for firewood consumption and forest production. The results showed that the consumption of farm-owned firewood is high in all regions. However, it was observed that the size of the farms and the small availability of idle areas hinder the significant expansion of forest production. Despite this, the observed trends demonstrated opportunities to improve forest production through the management of high-use multiple-use forests. Forest production can be a good source of income and diversification of farms and contribute to the Agenda 2030 of the UN. Implementing a sustainability index in small farms is an effective and simple tool for identifying bottlenecks and development opportunities.